PEMBUATAN PUPUK ORGANIK DARI LIMBAH PADAT PENYAMAKAN KULIT DI CV. CISARUA CIANJUR JAWA BARAT - Resty Arestya; Herry Suseno; RLM. Satrio Ari Wibowo (Politeknik ATK Yogyakarta, 2013)
Leather industry is one of industries supporting a country’s economy which has a negative side such as waste resulted from skin processing. Fleshing process is one those producing solid waste in the form of remnants of protein and fat that is potentially causing the pollution because of waste decomposition. CV. Cisarua located at Perintis Kemerdekaan 1001 Cianjur is one of the leather processing company in West Java. The company produces shoes leather and causes the emergence of some solid waste including: green fleshing waste from the early stages of leather processing, fleshing waste after liming process, shaving and WWT sludge waste as a by product of the waste water treatment. Those wastes were then processed into organic fertilizer. The processes of making organic fertilizer consist of material preparation, size reduction, pile preparation, inversion, maturation, milling, and drying under the sun. Efforts to maximize the process of making organic fertilizer were done by adding rotten rice as starter so that it could speed up the composting process in a laboratory scale. Feed quality testing is then known using physical, chemical and biological testing using marigolds plant/suring. Fertilizer was made using tannery solid waste added with (A) and without (B) rotten rice starter. Fertilizer A with 1.075% total nitrogen content using the composition of 40% cooked fleshing, 40% raw fleshing, 20% cow dung and starter 1:5 has met the requirements of SNI-09-7030-2004 (min. 0.4%). Fertilizer B with 0.9850% total nitrogen content using the composition 40% cooked fleshing, 20% raw fleshing, 10 shaving powder, 20% cow dung and 10% WWT sludge meets the requirements of SNI-09-7030-2004 (min. 0, 4%).